Effects of mindful physical activity on perceived exercise exertion and other physiological and psychological responses: results from a within-subjects, counter-balanced study - Solk, Payton; Auster-Gussman, Lisa A.; Torre, Emily; Welch, Whitney A.; Murphy, Karly; Starikovsky, Julia; Reading, Jean M.; Victorson, David E.; Phillips, Siobhan M. (Frontiers in Psychology, 2023)
Background Most adults are insufficiently active. Mindfulness training may increase moderate to vigorous physical activity (MVPA) adoption and adherence. However, physiological and psychological factors underlying these effects are not well understood. This study examined the effects of an acute bout of MVPA, mindfulness training, and combined MVPA and mindfulness training on physiological and psychological outcomes. Methods Healthy adults (N = 29, Mage = 28.6) completed 20-min counterbalanced conditions: (a) mindfulness training (MIND); (b) moderate intensity walking (PA), and (c) moderate intensity walking while listening to MVPA-specific guided mindfulness training (PAMIND). Heart rate (HR), Rating of Perceived Exertion (RPE), Feeling Scale (FS) and Blood Pressure (BP) were measured at rest, at regular intervals during each condition, and post-condition. Mindfulness, state anxiety, and self-efficacy were assessed pre- and post-condition. Results Average and peak HR, systolic BP (SBP), and RPE were significantly higher, and average and peak FS were significantly lower during the PA and PAMIND conditions compared to MIND (p < 0.001). Average RPE was significantly higher for PA compared to PAMIND (p < 0.001). Heart rate, feeling scale, body and mental events mindfulness, and self-efficacy for walking increased from pre to post (all p’s < 0.001) for all conditions. Time by condition interactions were significant for change in heart rate, mental events mindfulness, and state anxiety from pre- to post-condition. Conclusion The physiological response to MVPA and PAMIND were similar. However, RPE was rated lower in the PAMIND condition, which could have implications for MVPA adoption and maintenance. Future work should further explore RPE combining MVPA and mindfulness training.